27.7k views
2 votes
Simplify (square root 3)(^5 square root 3)

Simplify (square root 3)(^5 square root 3)-example-1
User Littlemad
by
5.4k points

2 Answers

3 votes

Answer:


3^{(7)/(10) }

Explanation:


√(3) *\sqrt[5]{3} = 3^1/2 x 3^1/5 = 3^(1/2 +1/5) = 3^7/10

User Freda
by
5.8k points
4 votes

Answer:

Explanation:

Exponent law:
a^(m)*a^(n)=a^(m+n)


(√(3) ) )*(\sqrt[5]{3})= 3^{(1)/(2)}*(3^{(1)/(5)})\\\\=3^{(1)/(2)+(1)/(5)}\\\\=3^{(1*5)/(2*5)+(1*2)/(5*2)}\\\\= 3^{(5)/(10)+(2)/(10)}\\\\=3^{(5+2)/(10)}\\\\=3^{(7)/(10)}

User Linello
by
6.4k points